Beyond screen time: Exploring effects of different smartphone use log metrics on situational well-being - Klingelhoefer, Julius; Gilbert, Alicia; Adrian, Christoph; Meier, Adrian (30th Annual Conference of the Media Uses and Effects division of the DGPuK, 2024)

Disconnecting from what? Digital detox effects beyond the device and application level - Klingelhoefer, Julius; Meier, Adrian (Digital Disconnection Studies Beyond Borders preconference of the 72nd Annual Conference of the ICA, 2022)

Disconnection strategies to improve productivity and well-being: A two-wave panel study - Klingelhoefer, Julius; Nguyen, Minh Hao; Geber, Sarah (74th Annual International Communication Association Conference, 2024)

Disconnect to recharge: Well-being benefits of digital disconnection in daily life - Gilbert, Alicia; Klingelhoefer, Julius; Meier, Adrian (2026)
Many aim to recalibrate and reduce their digital media use to improve well-being. We test the associations of digital disconnection with a set of positive, negative, and social indicators of well-being in a two-week experience sampling study. N = 237 participants reported on T = 12,407 situations in daily life. Results show that in situations in which participants disconnected more than usual, they reported higher affective well-being, energy, and social connectedness (within-person effects). In contrast, those who generally disconnected more than others reported no differences in well-being (between-person effects). Intrinsic motivation for disconnection positively moderated associations with affective well-being, energy, and social connectedness between persons. Disconnection was not related to stress, neither within nor between persons. The study further explores whether well-being effects differ depending on the aspects of digital media participants disconnected from. Overall, findings demonstrate how digital disconnection can achieve momentary – but not necessarily lasting – improvements in well-bein
https://cris.fau.de/converis/publicweb/Publication/335323869
Keywords: Digital disconnection; experience sampling; intrinsic motivation; media non-use; multilevel modelling; well-being

License to procrastinate: Is self-forgiveness for online procrastination driven by self-licensing or self-compassion? - Klingelhoefer, Julius; Meier, Adrian; Meltzer, Christine E.; Reinecke, Leonard (73rd Annual Conference of the International Communication Association, 2023)

Logging media non-use? A computational assessment of digital disconnection with smartphone logging data - Klingelhoefer, Julius; Gilbert, Alicia; Meier, Adrian; Adrian, Christoph; Reinecke, Leonard (13th Conference of the Media Psychology Division of the DGPs, 2023)

Log on, log off, repeat? Motivations and well-being effects of digital disconnection in everyday life - Klingelhoefer, Julius; Gilbert, Alicia; Meier, Adrian (73rd Annual Conference of the International Communication Association, 2023)

Mapping transdisciplinary views on disconnection studies: Perspectives from an interdisciplinary research collective - Ross, Morgan Quinn; Gilbert, Alicia; Klingelhoefer, Julius; Matassi, Mora; Nassen, Lise-Marie; Van Bruyssel, Sara; Verlinden, Alice (Key Themes in Digital Disconnection Research: Authenticity, Wellness, Datafication and Power Pre-Conference of the 73rd Annual International Communication Association Conference, 2023)

Mapping transdisciplinary views on disconnection studies: Perspectives from an interdisciplinary research collective - Ross, Morgan Quinn; Gilbert, Alicia; Klingelhoefer, Julius; Matassi, Mora; Nassen, Lise-Marie; Van Bruyssel, Sara; Parry, Douglas A (74th Annual International Communication Association Conference, 2024)

Measuring and mapping digital disconnection in daily life - Klingelhoefer, Julius; Gilbert, Alicia (29th Annual Conference of the Media Uses and Effects division of the DGPuK, 2023)

Mindful everyday disconnection — Well-being effects of being mindfully (dis-)connected - Klingelhoefer, Julius; Meier, Adrian (73rd Annual Conference of the International Communication Association, 2023)

Momentary motivations for digital disconnection: an experience sampling study - Klingelhoefer, Julius; Gilbert, Alicia; Meier, Adrian (Journal of Computer-Mediated Communication, 2024)
A much-discussed solution for undesirable (over-)use of mobile technologies lies in digital disconnection. Reasons for why individuals reduce their digital media use have been assessed mostly cross-sectionally without accounting for various disconnection practices across everyday situations. This study focuses on three motivations to disconnect that can vary between situations: to (a) avoid distractions, (b) improve wellbeing, and (c) be more present. A 14-day experience sampling study with 230 young adults (Mage ¼ 25.31, SD¼ 4.50) yielded 7,360 situations of disconnective behavior. Multilevel regression analyses show that motivations to avoid distractions and to be more present were relevant for disconnection on the situational level. However, a person’s average level of these motivations did not predict disconnective behavior. The wellbeing motivation was not associated with disconnection either between or within participants. Additional analyses explore variations across time and different levels of digital disconnection.
CRIS-Team Scopus Importer:2024-09-06
Keywords: digital disconnection; digital well-being; experience sampling; motivation; non-use

(Not) one more glance at my phone before I sleep: Effects of self-regulation of smartphone use on sleep displacement and arousal - Klingelhoefer, Julius; Jansen, Astrid; Vogelgesang, Jens (53rd DGPs Congress, 2024)

Optimizing mobile support for physical and mental health: A glimpse of mhealth projects - Yang, Ellie; de Segovia, David; Klingelhoefer, Julius; Mi, Estelle (Mobilizing Communication Rights for Humans, More-than Humans, and Beyond Mobile Division Preconference of the 74th Annual International Communication Association Conference, 2024)

Politics, power relations, and the UNGC: A relational orientation toward transparency - Harness, Delaney; Ganesh, Shiv; Klingelhoefer, Julius; Schnell, Mackenzie Taylor (NCA 109th Annual Convention, 2023)

Possible Futures All at Once: Time Frame and Time Lag in Short-Term Longitudinal Media Effects Research on Well-Being - Klingelhoefer, Julius; Gilbert, Alicia; Adrian, Christoph; Meier, Adrian (2025)
When assessing media effects, we seldomly consider how they change over time. Especially with the prevalence of smartphone use as short-term, fragmented media use, a systematic approach to temporal dimensions is crucial, particularly to understand mixed effects of smartphone use on well-being. We employ a multiverse approach to assess the influence of two central temporal dimensions in short-term longitudinal research: Time frame and time lag. We combine mobile experience sampling (T1 = 2,859, T2 = 7,708) and log data (K1 = 71,807, K2 = 259,004) from N1 = 84 and N2 = 192 participants. Building on theorizing on time in media effects research, we propose four patterns of how short-term effects unfold: they may follow processes of ephemerality (fleeting effects), inertia (delayed onset), or reversal (changing directions) – or there are no changes over time. We discuss theoretical implications and give practical recommendations for future studies, especially short-term longitudinal design
https://cris.fau.de/converis/publicweb/Publication/333591890
Keywords: experience sampling; media effects; multilevel; multiverse analysis; short-term longitudinal designs; time; well-being

Senators With Superpowers? The Role of Authenticity and Appropriateness Perceptions for the Sharing of Heroization Memes in the Political Context - Klingelhoefer, Julius; Stein, Jan-Philipp; Feiler, Thomas; Yeo, Jiyeon; Appel, Markus (72nd Annual Conference of the ICA, 2022)

Social media and well-being at work, at home, and in-between: a review - Klingelhoefer, Julius; Meier, Adrian (Research handbook on digital sociology, 2023)
With increasing relevance of collaborative technologies in the workplace and flexible work arrangements, concerns and hopes about associations between social media use and well-being arise. Social media can introduce content and demands from the work context into the home and vice-versa. This narrative review of k = 39 publications addresses work-inconsistent and home-inconsistent social media use, particularly during remote work. The reviewed studies show that social media use can be associated with negative outcomes such as stress. At the same time, many studies found associations with beneficial outcomes such as higher job satisfaction. These conclusions are limited by the predominantly cross-sectional survey designs and inconsistent conceptualization and measurement of social media use. We suggest improvements and call for more longitudinal and experimental studies to advance the understanding of social media use and well-being at the work-home interface.<br
Keywords: social media; ICTs; well-being; work-home interface; remote work; narrative review

The effects of sexist comedy on benevolent sexism and domain identification. - Weber, Silvana; Klingelhoefer, Julius; Appel, Markus (70th Conference of the International Communication Association, 2020)

The Forgotten SDGs - Harness, Delaney; Klingelhoefer, Julius; Ganesh, Shiv (The mediation of sustainability: Development goals, social movements, and public dissent, 2023)

The Forgotten SDGs: Competing Priorities in Sustainability Reporting - Harness, Delaney; Klingelhoefer, Julius; Ganesh, Shiv (NCA 108th Annual Convention, 2022)

The PowerPoint imagination: Visualization and managerial vocabularies in sustainability reports - Ganesh, Shiv; Harness, Delaney; Schnell, Mackenzie Taylor; Klingelhoefer, Julius; James, Samantha H; Palakshappa, Nitha (NCA 109th Annual Convention, 2023)

Train like a man: The interplay of precarious manhood and social comparisons in Instagram sports-posts - Klingelhoefer, Julius; Weber, Silvana (28th Annual Conference of the Media Uses and Effects division of the DGPuK, 2022)